What is the value of the following sum?

$$\frac{1}{1!}+\frac{1+2}{2!}+\frac{1+2+3}{3!}+ \cdots$$

The possible answers are:

A. $e$

B. $\frac{e}{2}$

C. $\frac{3e}{2}$

D. $1 + \frac{e}{2}$

I tried to expand the options using the series representation of $e$ and putting in $x=1$, but I couldn't get back the original series. Any ideas?

  • 1
    $\begingroup$ Suggestion - use $n(n+1)/2 = 1+ \cdots + n$. $\endgroup$ – peter a g Jan 2 '16 at 17:11
  • $\begingroup$ Always check the numerator's degree ! If it is 3 , then you will have to have 4 constants A,B,C,D $\endgroup$ – Angelo Mark Jan 2 '16 at 17:34
  • 2
    $\begingroup$ Nicely rendered as $$\frac11+\frac{1+2}{1\times2}+\frac{1+2+3}{1\times2\times3}+\frac{1+2+3+4}{1 \times 2\times3\times4}+\cdots$$ $\endgroup$ – user65203 Jan 2 '16 at 17:49
  • 1
    $\begingroup$ Note that as that this is a multiple-choice question, all but (C) can be quickly eliminated. $\endgroup$ – Brian Tung Jan 2 '16 at 18:26

Clearly the $r^{th}$ numerator is $1+2+3+...+r= \frac{r(r+1)}{2}$ .

And the $r^{th}$ denominator is $r!$.

Thus $$\displaystyle U_r=\frac{\frac{r(r+1)}{2}}{r!}=\frac{r(r+1)}{2r!}$$

Since the degree of the numerator is $2$ , use partial fractions to find $A,B,C$ such that (If you use partial fractions up to $(r-3)!$ , its' coefficient will be zero when comparing coefficients.)

$\displaystyle U_r=\frac{r(r+1)}{2r!}=\frac{A}{(r-2)!}+\frac{B}{(r-1)!}+\frac{C}{r!}$

$\displaystyle (2r!)\times U_r=(2r!)\times \frac{r(r+1)}{2r!}=(2r!)\times \frac{A}{(r-2)!}+(2r!)\times \frac{B}{(r-1)!}+(2r!)\times \frac{C}{r!}$

So $\displaystyle r(r+1)=r!\times \frac{2A}{(r-2)!}+r!\times \frac{2B}{(r-1)!}+r!\times \frac{2C}{r!}$


Now observe that

$r!=1\times 2\times 3\times .... \times (r-2)\times(r-1)\times r $

$\Rightarrow r!=(r−2)! ×(r−1)r $ and

$ \Rightarrow r!=(r−1)!×r $


So $\displaystyle r(r+1)=(r−2)! ×(r−1)r \times \frac{2A}{(r-2)!}+(r−1)!×r\times \frac{2B}{(r-1)!}+r!\times \frac{2C}{r!}$

So $\displaystyle r^2+r = 2A(r-1)r+2Br+ 2C $

Clearly $C=0$ , $B=1$ and $A=\frac{1}{2}$

So $\displaystyle U_r=\frac{r(r+1)}{2r!}=\frac{1}{2(r-2)!}+\frac{1}{(r-1)!}$

$\displaystyle \sum_{r=2}^{\infty}U_r= \frac{1}{2} \left( \frac{1}{0!}+\frac{1}{1!}+\frac{1}{2!}+.....\right)+\left( \frac{1}{1!}+\frac{1}{2!}+\frac{1}{3!}+.....\right)$

$\displaystyle \sum_{r=2}^{\infty}U_r= \frac{1}{2} \left( e\right)+\left( e-1\right)$

$\displaystyle \sum_{r=1}^{\infty}U_r= U_1+\frac{1}{2} \left( e\right)+\left( e-1\right)=1+\frac{e}{2}+e-1 =\frac{3e}{2}$

  • 1
    $\begingroup$ How did you find $U_r$ and why did you write it into partial fractions having specific denominators $\endgroup$ – Taylor Ted Jan 2 '16 at 17:25
  • 1
    $\begingroup$ Clearly $1+2+3+...+r= \frac{r(r+1)}{2}$ . Thus $ U_r=\frac{r(r+1)}{2r!}$ . Partial fraction is a trick for these kinda Q' s which I learnt in Advanced levels. It works for these type of questions. It is very easy. Nothing to remember $\endgroup$ – Angelo Mark Jan 2 '16 at 17:29
  • $\begingroup$ What is AL's ?.Does this trick work for all questions like these(series summing) $\endgroup$ – Taylor Ted Jan 2 '16 at 17:31
  • $\begingroup$ Yes It works when factorials are there ! $\endgroup$ – Angelo Mark Jan 2 '16 at 17:32
  • $\begingroup$ Always check the numerator's degree ! If it is 3 , then you will have to have 4 constants $A,B,C,D$ $\endgroup$ – Angelo Mark Jan 2 '16 at 17:34

Hint...start by writing out the series for $xe^x$ and differentiate twice

  • 1
    $\begingroup$ How did you know which function to choose $\endgroup$ – Taylor Ted Jan 2 '16 at 17:26
  • 3
    $\begingroup$ In order to create the extra factors $n+1$ and $n$ in the numerator, I am starting with $\frac{x^{n+1}}{n!}$, therefore we need the series for $x\times e^x$, and we differentiate twice to get the factors. I hope this helps! $\endgroup$ – David Quinn Jan 2 '16 at 17:38
  • $\begingroup$ When you differentiate twice the series you started with it becomes $\frac{n(n+1)x^{n-1}}{n!}$. What did you put x in here? $\endgroup$ – Taylor Ted Jan 3 '16 at 2:22


Hence the sum is

$$\frac e2+e.$$

Note that the first summation in the RHS must be started at $k=2$ (or use $1/(-1)!:=0$).


Starting with $\sum_{i=1}^ni=\frac{n(n+1)}{2}$, the sum simplifies to \begin{align*} z=\frac{1}{2}\sum_{i=1}^\infty \frac{i(i+1)}{i!}&=\frac{1}{2}\sum_{i=1}^\infty \frac{i+1}{(i-1)!}\\ &=\frac{1}{2}\sum_{i=0}^\infty\frac{i+2}{i!}\\ &=\frac{1}{2}\sum_{i=0}^\infty\left(\frac{i}{i!}+\frac{2}{i!}\right)\\ &=\frac{1}{2}\left(\sum_{i=1}^\infty\frac{1}{(i-1)!}+\sum_{i=0}^\infty\frac{2}{i!}\right)\\ &=\frac{1}{2}\left(\sum_{i=0}^\infty\frac{1}{i!}+2\sum_{i=0}^\infty\frac{1}{i!}\right)\\ &=\frac{1}{2}(e+2e)=\frac{3e}{2} \end{align*}


Your sum is $$\sum_{n = 1}^{\infty} \sum_{k = 1}^{n} \frac {k} {n!} = \sum_{n = 1}^{\infty} \frac {n + 1} {2 (n - 1)!} = \sum_{n = 0}^{\infty} \frac {n + 2} {2 n!} = \frac {3e} {2}.$$

  • 1
    $\begingroup$ Last equality a little quick, IMO. $\endgroup$ – user65203 Jan 2 '16 at 17:39
  • $\begingroup$ Because $$\sum_{n = 0}^{\infty} \frac {n + 2} {2 n!} = \sum_{n = 0}^{\infty} \frac {1} {2 (n - 1)!} + \frac {1} {n!} = \frac {e} {2} + e.$$ I don't have paper, I don't have pen, I'm sick and in bed, I am eating my sandwich so I'm writing with one hand. $\endgroup$ – user98186 Jan 2 '16 at 17:43

You want calculate $\sum_{k=1}^\infty\frac{k(k+1)}{2(k!)}=\frac{1}{2}\sum_{k=1}^\infty\frac{k+1}{(k-1)!}=\frac{1}{2}\sum_{k=0}^\infty\frac{k+2}{k!}$...(*)

But, as $e^x=1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+\cdots$, then $x^2e^x=x^2+x^3+\frac{x^4}{2!}+\frac{x^5}{3!}+\cdots$. Deriving both sides give us $x^2e^x+2xe^x=2x+3x^2+\frac{4x^3}{2!}+\frac{5x^4}{3!}+...$. Thus, evaluating at $x=1$: $e+2e=\sum_{k=0}^\infty\frac{k+2}{k!}$.

Substituying the last in (*) give us finally $\frac{3e}{2}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.